Глухівчанин А. Лосенко – ректор Імператорської російської академії мистецтв - Ковальов, О.Є. (Сіверщина в історії України, 2020)
На основі педагогічних видань та історичних архівних документів досліджується життєвий шлях одного із видатних художників другої половини XVIII ст. – українського живописця, педагога, основоположника російського історичного живопису А.П. Лосенка. Antin Losenko was born on August 10, 1737 in the family of a Ukrainian Cossack in Hlukhiv, the capital of Hetmanate. In 1738, a famous singing school was opened there, that prepared singers for Ukrainian (Malorosiiskykh) choirs and a court singing chapel. Antin studied singing and instrumental music at this Hlukhiv school of singing. When in 1744 the conductor of the royal chapel traveled about Ukraine, recruiting boys with perfect voices, his attention was attracted by seven-year-old orphan Antin Losenko, Kyrylo Holovachevskyi and Ivan Sabluchko. Until the 16th year of his life, Antin sang the old cantos, new concerts in the St. Petersburg court chapel and he received a serious music education, played the flute. He was friends with Oleksii Rozum. When he has some free time he came to the workshop of the painter Olkhovskyi, where he took paid lessons. When the age-old change of voice happened, he was sent for training to the portraitist Ivan Arhunov (the servant of Earl Petro Sheremetiev). Five years later, Count Ivan Shuvalov enrolled Losenko at the St. Petersburg Academy of Arts, where he studied under the guidance of French artists Louis-Joseph Le-Lorraine and Jean-Louis Devellier. In 1760, Losenko painted portraits of the President of the St. Petersburg Academy of Arts, Count Ivan Shuvalov, the poet Oleksandr Sumarokov. Beginning from September of the same year he perfected his mastery with the portraitist Jean Retou in Paris (where he was tutored by D. Holitsyn). Antin deliberately wrote: «Losenko is from Ukraine». Antin Losenko created a great picture according to the gospel story there «Wonderful Fishing». The Ukrainian did not have his own funds, he was the first pensioner of the Academy, so he depended on the officials. When, in the autumn of 1762, he was not sent money, Losenko walked home in despair. Through the lands of France, Holland, Germany the young man walked in late autumn and in winter, carrying the biggest treasure – the picture «Wonderful fishing». Petersburg was impressed with the painting, the queen bought it. At the same year he painted a portrait of the founder of the first Russian public theater, Fyodor Volkov, and the actor Yakov Shumsky. For the next three years, Losenko studied in Paris again. His teacher, Jean Rheet, went blind, so he was engaged in the workshop of historical painting of Joseph-Marie Wien. There he painted «Adonis’s Death», «Andrew the First Called (Pervozvanny)» (both in 1764), «The Sacrifice of Abraham» (1765). In France, Losenko’s talent was recognized and appreciated with three medals from the Paris Academy of Arts. From 1766 he studied antiquity and copied the masters of the Renaissance in Italy, painted «Zeus and Thetis» (1769). In 1769, Losenko returned to St. Petersburg, where he was asked to create a painting for the title of Academician of Historical Painting (the plot was to be on the subject of the Bible, ancient or mythological). The artist first took a story from the history of Kyivan Rus – «Volodymtr and Rohnida», claiming equality of national history with the history of the ancient world. He received the title of Academician for the painting, which Catherine II bought for a private collection, and he held the position of Associate Professor of the St. Petersburg Academy of Arts. Although today the work seems to be a naive sentimental parody, but since its painting, Losenko has been proclaimed the «creator of the historical school». In 1772 he became a professor and director (together with the French sculptor Nicolas-François Gillet) of the Petersburg Academy of Arts. Antin Losenko was the first in the Russian Empire to create a manual on artistic anatomy called «Explanation of the short proportion of man, based on a reliable study of the different proportions of ancient statues, by efforts of the Imperial Academy of Arts and the professor of painting Mr. Losenko for the benefit of adolescence». He also prepared recommendations for working on the historical painting. His pedagogical activity, as well as his textbook (used until the middle of the nineteenth century), significantly influenced the development of art education in the Russian Empire. The work on rector’s post took a long time, and Losenko did it honestly. In addition, there were a lot of the intrigues, the money lessness, because the artist did not have time to paint.